2020
DOI: 10.3991/ijim.v14i12.15583
|View full text |Cite
|
Sign up to set email alerts
|

An Integration of "Online Interactive Apps" for Learning Application of Graph Theory to Enhance Creative Problem Solving of Mathematics Students

Abstract: An Integration of “Online Interactive Apps” for learning can be a disruptive learning innovation in higher education. The material of the application of graph theory course has application topics in the real world. How students use the application can be used as a measure of creative problem solving. Mixed method was used in the study. The first phase of the study used one group non-randomized design pre-test and post-test. Participants were students who took courses in the application of graph theory. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Prior studies have indicated that mobile applications are an effective tool for promoting students' creative thinking. For instance, [19] found that the application of interactive apps in mathematics courses enhanced students' creative problem-solving abilities. Similarly, integrating mobile applications into realistic mathematics is effective in enhancing learners' creative thinking ability [20].…”
Section: Mobile Application and Creative Thinkingmentioning
confidence: 99%
“…Prior studies have indicated that mobile applications are an effective tool for promoting students' creative thinking. For instance, [19] found that the application of interactive apps in mathematics courses enhanced students' creative problem-solving abilities. Similarly, integrating mobile applications into realistic mathematics is effective in enhancing learners' creative thinking ability [20].…”
Section: Mobile Application and Creative Thinkingmentioning
confidence: 99%
“…This is due to universities being at the academic levels that are most ready to implement information technology comprehensively (Prasetya et al, 2020). The research results (Kashefi et al, 2011;Kashefi, Ismail and Yusof, 2012;Lim and Han, 2020;Wahyuningsih et al, 2020) reported that the CPS process through a blended learning context could increase active student involvement in the learning process. The results of this study illustrate that the CPS method in the context of blended learning can be a learning model that lecturers can use to promote student learning outcomes for prospective teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Model CPS menerapkan proses pengembangan kreativitas dan inovasi terhadap solusi yang dapat memecahkan permasalahan (Kapoor et al, 2020). Tahapan pada model CPS mendukung terhadap pemecahan masalah ketika proses pembelajaran praktik (Wahyuningsih et al, 2020) karena adanya proses pendekatan atau metode untuk menangani masalah secara imajinatif agar dapat menghasilkan suatu tindakan efektif dan efisien (Sulaeman et al, 2021); (Harefa et al, 2020). Sehingga model pembelajaran CPS yang berbasis pemecahan masalah pada langkah-langkahnya sesuai dengan karakteristik pembelajaran instalasi motor listrik yang menerapkan pembelajaran teori (pengetahuan) serta praktik (sikap dan keterampilan).…”
unclassified